ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PELANGGAN KERETA API PANGRANGO KELAS EKSEKUTIF RUTE BOGOR-SUKABUMI - Jihan, Nurul Syah; Maksudi, Beddy Iriawan; Purnmasari, Irma (Jurnal Governansi, 2019)
The purpose of this study is to analyze how the servive quality is available at the Bogor-Sukabumi Pangrango train. The theory in this study is to use the theory of service quality perceived by consumers from Zeithaml, Parasuraman and Berry which states that service quality can be measured through 5 dimensions namely tangibles, reliability, empathy, responsiveness and assurance. Satisfaction of the community according to Fandy Tjiptono is service performance, product quality, and price. The research method uses the associative method using quantitative analysis. Data was collected through observation, interviews, and questionnaires. Correlation test used Spearman Rank test. This research used technique to collect data with a population of service users as many as 593 people, the study sample was 86 respondents. The results of this study obtained an assessment number for variable X, namely 3.84 with good assessment criteria and Y variable is 3.83 with good assessment criteria. In the Spearman Rank correlation test obtained a correlation value of 0.674. The correlation value of 0.674, is strong with the direction of a positive relationship, meaning that the relationship is in the same direction. The amount of the correlation/relationship (R) is equal to 0.674, while the coefficient of determination (R Square) is 0.4542. It is known that the quality of service affects people’s satisfaction by 45.42%, and by 54.58% by being influenced by other factors. Keywords: Service Quality, Community Satisfaction.